2010
DOI: 10.1016/j.psyneuen.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol, reaction time test and health among offshore shift workers

Abstract: We found no increase in health complaints from swing shift or reaction time in the shift from night to day work. Recovery from night shift takes longer time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 125 publications
(154 reference statements)
6
100
2
3
Order By: Relevance
“…However, following prolonged exposure to the stressors, the body's biological systems could mount a counter-regulatory response (dysregulation) such that the cortisol output rebounds to less than normal. The results from the current study are consistent with this hypothesis and in agreement with other studies that investigated cortisol rhythms in shift workers and found that the cortisol awakening response is decreased and evening cortisol levels are increased during shift work 19,25,35) . In a study of police officers from the current sample, the association between short-term shift work (3, 5, 7 and 14 days prior to saliva collection) and waking cortisol was examined and waking salivary cortisol levels were lower among night or afternoon shift officers compared to those on day shift 28) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, following prolonged exposure to the stressors, the body's biological systems could mount a counter-regulatory response (dysregulation) such that the cortisol output rebounds to less than normal. The results from the current study are consistent with this hypothesis and in agreement with other studies that investigated cortisol rhythms in shift workers and found that the cortisol awakening response is decreased and evening cortisol levels are increased during shift work 19,25,35) . In a study of police officers from the current sample, the association between short-term shift work (3, 5, 7 and 14 days prior to saliva collection) and waking cortisol was examined and waking salivary cortisol levels were lower among night or afternoon shift officers compared to those on day shift 28) .…”
Section: Discussionsupporting
confidence: 93%
“…A study of total cortisol levels from hair samples 27) compared 33 shift workers and 89 day workers where shift workers were shown to have higher hair cortisol levels than day workers but the hair cortisol in this study measured total amount of cortisol released over the last 3 months while our measure concerns how much is released in response to the awakening signal. In a study of chronic stress associated with unemployment, unemployed subjects had higher morning and lower evening salivary cortisol levels compared to employed subjects 35) . In a sample of 100 university students, those who perceived a higher level of chronic stress due to workload had higher early morning cortisol increase after awakening than those who did not 36) .…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, the normal circadian patterns of cortisol were augmented by Fiberpro with peaks in the morning and troughs in the evening, and these patterns persisted even after the discontinuation of supplementation. Cortisol is a hormone that is released from the adrenal cortex in response to various stressors that activate the hypothalamic-pituitary-adrenal (HPA) axis [9] [10] [11]. As such, it is a well-known biomarker of stress.…”
Section: Discussionmentioning
confidence: 99%
“…The normal pattern is that sleep is reduced by approximately 2 hours when working early morning or night shifts (11). Previous studies have already demonstrated that workers in isolated environments are able to complete adapt to night shifts within a week (9,12,13). This is a much faster adaptation than what happens with workers in less isolated environments, where the adaptation normally takes between 8-14 days.…”
Section: Introductionmentioning
confidence: 99%
“…The cortisol awakening response (CAR), defined as the period of cortisol secretory activity in the first 30 to 60 minutes immediately post-awakening, is presumed to be determined by circadian influences but will also reflect phasic psychophysiological processes specific to the waking-up Cortisol levels in construction workers in the Arctic process (6,8). Saliva cortisol sampled immediately after awakening and during the working period is a good indicator for any changes in diurnal rhythm associated with different working schedules (9).…”
Section: Introductionmentioning
confidence: 99%